(untitled) (UUM Journal of Legal Studies, 2020)
Industrial relations is one of the most delicate and complex issues in a modern industrial society. Industrial progress is well-nigh impossible without the cooperation of the labour force and the harmonious relationship between employers and employees. Therefore, it is in the interest of all to create and maintain the good relationship between employers and employees. Malaysia, as one of the South East Asian countries, hopes to be a high-income nation by 2024. In order to achieve the status of high income nation, the government of Malaysia has introduced the Economic Transformation Programme (ETP). ETP will help Malaysia to triple its Gross National Income (GNI) from RM 660 billion in 2009 to RM 1.7 trillion in 2020. The status of high income nation is said to be achieved, among others, via innovation, creativity, higher productivity, new technology and the development of a multi-skilled and highly skilled workforce as well as healthy industrial relations. As such, in underlining industrial relations in a high-income nation, this article is an attempt to examine the role of the Malaysian industrial relations of today. It will also portray whether changes are required in Malaysian industrial relations in order to be relevant in a high-income nation.